Respuesta :

Hi1315

Answer:

x = -5

y = -2

Step-by-step explanation:

-3x + 4y = 7 ⇒ ( 1 )

7x - 12y = -11 ⇒  ( 2 )

Multiply the equation ( 1 ) by 3.

( 1 ) × 3

3( -3x + 4y = 7 )

-9x + 12y = 21  ⇒ ( 3 )

Let us find the value of x.

Add equations ( 2 ) & ( 3 ).

( 2 ) + ( 3 )

7x - 12y - 9x + 12y = - 11 + 21

Combine like terms.

-2x = 10

Divide both sides by -2.

x = -5

Let us find the value of y.

For that, let us use equation ( 1 ) and replace x with -5 and make y the subject.

- 3x + 4y = 7

-3 × -5 + 4y = 7

15 + 4y = 7

Subtract 15 from both sides.

4y = 7 - 15

4y = -8

Divide both sides by 4.

y  = -2

ACCESS MORE